PERSEPSI MASYARAKAT TERHADAP PROGRAM KEMITRAAN DAN BINA LINGKUNGAN (PKBL) PTPN VII UNIT USAHA REJOSARI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Musoleha, Tati; Hasanuddin, Tubagus; Listiana, Indah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This research was aimed to analyze PKBL of PTPN VII Rejosari’s Business Unit, community’s and company’s management perception to PKBL, and the factors that influence the community’s perception to PKBL. This research was conducted at Rejosari Village, Natar Subdistrict, South Lampung Regency. This research used survey method and the data was collected from April to May 2014. The research respondents were 84 households that were chosen randomly. The data was analyzed by descriptive and path analysis. The result showed that PKBL by PTPN VII Rejosari’s Business Unit applied to two sectors: economic and environmental. PKBL granted directly to the recipient and the dissemination of information through the village officials and employees. The ccommunity’s perception of PKBL by PTPN VII Rejosari’s Business Unit was good enough because the program was given in various forms of assistances that was useful to community and the environment. Perception of the company's management on PKBL was also good for helping and providing great benefits to community and the environment. The factors that influenced to the community’s perception on PKBL by PTPN VII Rejosari’s Business Unit were personal age, personal educational level, and personal knowledge level. The most influencing factor of community’s perception on PKBL was personal age. Key words: community, development, partnership, perception, PKBL